KEBIJAKAN PENDIDIKAN SEKULER ERA MENTERI PENDIDIKAN DAOED JOESOEF 1978-1983 - Ablyyu Riwanto; Iin Nur Zulaili (Qurthuba: The Journal of History and Islamic Civilization, 2022)
Abstract: This is an article that discusses the history of Indonesian secular education. The researcher focuses on three main issues, namely: (1) What is the biography of the Minister of Education and Culture Daoed Joesoef? (2) How were the secular policies during the reign of the Minister of Education and Culture Daoed Joesoef? (3) What is the impact on Muslims of policies that are considered secular during the era of the Minister of Education Daoed Joesoef. Researchers use historical, political science and sociological approaches using the theory of secularism. The results obtained in this study are (1) Childhood and education received and career path of the Minister of Education Daoed Joesoef along with his thoughts while serving as a minister. (2) Policies that are considered secular, such as eliminating holidays during the month of Ramadan and banning headscarves for schoolgirls. (3) The impact on Muslims with the issuance of policies that are considered secular, such as many students being expelled from school related to policies issued by the Minister of Education Daoed Joesoef. Keywords: Daoed Joesoef, policy, secular